ANALISIS NADA DALAM KETERAMPILAN BERBICARA BAHASA MANDARIN SISWA KELAS VIII SMP IT CHENG HOO KAB GOWA - Muhammad Rifky Saputra; Jufri Ap; Asmuliyati Nahnu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the difficulties in pronouncing Mandarin tones among eighth- grade students at SMP IT Chenghoo, Gowa Regency, using the Praat application. This research employed a descriptive qualitative method. Data were collected through classroom observations, questionnaires, voice recordings, and documentation. The collected data were analyzed using the Praat application to examine students' pitch patterns and the stability of their intonation when pronouncing Mandarin tones. The results indicate that most students still experienced difficulties in producing Mandarin tones accurately, particularly the second tone and the third tone. The identified errors included incorrect tone direction, unstable pitch variation, and difficulties in pronouncing tone combinations within sentences. Furthermore, the questionnaire results revealed that the students had relatively good learning motivation, and that the teacher played an important role in supporting students by providing direct and repeated pronunciation demonstrations. The use of the Praat application enabled the researcher to analyze pronunciation errors more objectively through speech visualization and pitch contour analysis. Therefore, the use of the Praat application, combined with continuous pronunciation practice, can help improve students' ability to pronounce Mandarin tones accurately.